Pests and resistance: The biology and control of supervectors and superpests - Anna E. Whitfield; Dorith Rotenberg (Current Opinion in Insect Science, 2023)

A call to arms: novel strategies for thrips and tospovirus control - Marlonni Maurastoni; Jinlong Han; Anna E Whitfield; Dorith Rotenberg (Current Opinion in Insect Science, 2023)

Evaluating the performance of the MODIS Leaf Area Index (LAI) product over a Mediterranean dryland planted forest - M. Sprintsin; A. Karnieli; P. Berliner; E. Rotenberg; D. Yakir; S. Cohen (International Journal of Remote Sensing, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Quality analysis applied on eddy covariance measurements at complex forest sites using footprint modelling - C. Rebmann; M. Göckede; T. Foken; M. Aubinet; M. Aurela; P. Berbigier; C. Bernhofer; N. Buchmann; A. Carrara; A. Cescatti; R. Ceulemans; R. Clement; et al. (Theoretical and Applied Climatology, 2005)

Carbon sequestration in arid‐land forest - J. M. GRÜNZWEIG; T. LIN; E. ROTENBERG; A. SCHWARTZ; D. YAKIR (Global Change Biology, 2003)
Rising atmospheric CO 2 concentrations may lead to increased water availability because the water use efficiency of photosynthesis (WUE) increases with CO 2 in most plant species. This should allow the extension of afforestation activities into drier regions. Using eddy flux, physiological and inventory measurements we provide the first quantitative information on such potential from a 35‐year old afforestation system of Aleppo pine ( Pinus halepensis Mill.) at the edge of the Negev desert. This 2800 ha arid‐land forest contains 6.5 ± 1.2 kg C m −2 , and continues to accumulate 0.13–0.24 kg C m −2 yr −1 . The CO 2 uptake is highest during the winter, out of phase with most northern hemispheric forest activity. This seasonal offset offers low latitude forests ∼10 ppm higher CO 2 concentrations than that available to higher latitude forests during the productive season, in addition to the 30% increase in mean atmospheric CO 2 concentrations since the 1850s. Expanding afforestation efforts into drier regions may be significant for C sequestration and associated benefits (restoration of degraded land, reducing runoff, erosion and soil compaction, improving wildlife) because of the large spatial scale of the regions potentially involved (ca. 2 × 10 9 ha of global shrub‐land and C4 grassland). Quantitative information on forest activities under dry conditions may also become relevant to regions predicted to undergo increasing aridity.

Comparison of ketorolac and diclofenac in the treatment of renal colic - E. Cohen; R. Hafner; Z. Rotenberg; M. Fadilla; M. Garty (European Journal of Clinical Pharmacology, 1998)